Comparative Analysis of Bacterial and Algal Treatment in Attached and Suspended Systems for Egg-Washing Wastewater Treatment - Shivaram, Karthik B.; Nakatsu, Cindy H.; Yakamercan, Elif; Engel, Bernard A.; Huwe, Adam P.; Brunnquell, John; Simsek, Halis (Amer Chemical Soc, 2025)
Egg-washing wastewater treatment is challenging due to high nutrients and organic matter from manure and broken eggs during washing. This study evaluated the performance of attached and suspended growth treatment systems, focusing on the impact of hydraulic retention time (HRT) on the treatment efficiency. Various rectangular and column reactors were employed, and moving bed biofilm reactor (MBBR) media and algae-bacteria consortia were used. Bacterial and bacterial-algal (Chlorella vulgaris) inocula, across different HRTs of 12, 24, and 48 h in column reactors and 2, 4, and 8 days in rectangular reactors, were tested. The reactors were aerated using a pump running at 5 psi (pounds per square inch) at room temperature. Algae-bacteria inoculum outperformed the standalone bacteria inoculum in removing both inorganic nitrogen and phosphorus. In the column reactor, total dissolved nitrogen removal peaked at 53.8% with bacterial inoculum at a 2 day HRT. Phosphorus removal exceeded 82% at a 4 day HRT in MBBR systems. Both reactor types demonstrated similar chemical oxygen demand (COD) removal rates, with up to 90% COD removal in MBBR at a 2 day HRT. When the COD loads reached 12,000 mg/L, attached growth systems showed greater resilience to these shock loads than suspended growth systems.
Keywords: egg washing wastewater; hydraulic retention time; solids retention time; Chlorella vulgaris; MBBR; algae; bacteria